2018
DOI: 10.1093/mnras/sty3091
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale study of star formation in Messier 33

Abstract: For the Local Group Scd galaxy M 33 this paper presents a multi-scale study of the relationship between the monochromatic star formation rate (SFR) estimator based on 12 µm emission and the total SFR estimator based on a combination of far-ultraviolet and 24 µm emission. We show the 12 µm emission to be a linear estimator of total SFR on spatial scales from 782 pc down to 49 pc, over almost four magnitudes in SFR. These results therefore extend to sub-kpc length scales the analogous results from other studies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Williams et al (2018) derived a SFR of 0.25 +0.01 −0.07 M yr −1 using the FUV+24 µm method (Leroy et al 2008) and 0.33 +0.05 −0.06 M yr −1 from a global fit and the MAGPHYS code (Da Cunha et al 2008). Elson et al (2019) derive a SFR of 0.34 +0.08 −0.07 M yr −1 using 12 µm estimates and the calibrated global WISE W3 luminosities to SFRs presented in Cluver et al (2017), and (0.44 ± 0.10) M yr −1 , based on the linear relation between 100 µm emission and total SFR presented by Boquien et al (2010).…”
Section: Star-formation Ratementioning
confidence: 99%
“…Williams et al (2018) derived a SFR of 0.25 +0.01 −0.07 M yr −1 using the FUV+24 µm method (Leroy et al 2008) and 0.33 +0.05 −0.06 M yr −1 from a global fit and the MAGPHYS code (Da Cunha et al 2008). Elson et al (2019) derive a SFR of 0.34 +0.08 −0.07 M yr −1 using 12 µm estimates and the calibrated global WISE W3 luminosities to SFRs presented in Cluver et al (2017), and (0.44 ± 0.10) M yr −1 , based on the linear relation between 100 µm emission and total SFR presented by Boquien et al (2010).…”
Section: Star-formation Ratementioning
confidence: 99%
“…Approaching the excellent spatial resolution (∼18 pc) of the ALMA maps for the SFR is not possible, but the use of the 8 μm instead of 24 μm emission to trace the SFR mitigates this issue by a factor of 2 (Maragkoudakis et al 2017), and so we chose the 8 μm band for our analysis because of its higher angular resolution (2 4, or 43 pc) compared to that of the 24 μm data (6 0, or 108 pc). Moreover, Elson et al (2019) showed that the 8 μm PAH emission is a robust SFR tracer down to physical spatial resolutions of 49 pc. PAH emission represents generally more than 70% of the 8 μm emission (Calzetti 2011) and dominates by more than a factor of 100 above the warm dust emission and about a factor of 5 above the stellar continuum (Li & Draine 2001;Dale et al 2005;Young et al 2014a).…”
Section: Validity Of Using 8 μM Pah Data As Star Formation Rate Tracermentioning
confidence: 99%
“…PAH emission represents generally more than 70% of the 8 μm emission (Calzetti 2011) and dominates by more than a factor of 100 above the warm dust emission and about a factor of 5 above the stellar continuum (Li & Draine 2001;Dale et al 2005;Young et al 2014a). As a consequence, PAH emission (and in particular from the Spitzer 8 μm band) has been used in the literature to estimate SFR in galaxies (Calzetti et al 2005;Wu et al 2005;Pérez-González et al 2006;Zhu et al 2008;Pancoast et al 2010;Calzetti 2011;Kennicutt & Evans 2012;Young et al 2014a;Cluver et al 2017;Kokusho et al 2017;Maragkoudakis et al 2017;Hall et al 2018;Elson et al 2019;Mahajan et al 2019). Nevertheless, there may be variations from galaxy to galaxy, due to metallicity or different beam filling factors (Calzetti et al 2005;Engelbracht et al 2005;Pérez-González et al 2006;Young et al 2014a), so it is necessary to assess the validity of the 8 μm PAH emission as a reliable SF tracer in Cen A.…”
Section: Validity Of Using 8 μM Pah Data As Star Formation Rate Tracermentioning
confidence: 99%
“…Some examples include studies based on The H i Nearby Galaxy Survey (THINGS, Walter et al 2008) and its data (Bigiel et al 2008;Leroy et al 2008). Other recent works include Zheng et al (2013) on the regulation of star formation; as well as Thilker et al (2007) and Holwerda et al (2012) on the link between star formation and H i morphology (implying a physical link; Heiner et al 2008); studies of multi-scale star formation and H i (Elson et al 2019); the link between SFR and gas based on jellyfish galaxies (Jáchym et al 2019;Ramatsoku et al 2019Ramatsoku et al , 2020Moretti et al 2020); and Bacchini et al (2019) on the link between SFR and H i volume densities.…”
Section: Introductionmentioning
confidence: 99%